Towards a Local Plan of Prevention and Attention of School Absenteeism in Latin America - Razeto-Pavez, Alicia Cristina; García-Gracia, Maribel (Revista Electrónica Educare, 2020)
School absenteeism is one of the most growing socio-educational problems in schools in the Latin and Central American region. Several studies show the harmful effects it has on the students’ educational performance and their future development opportunities. However, insufficient progress has been made in the formulation of intervention-oriented plans on the subject, and schools are alleged to be responsible for this situation. They are also claimed as scenarios, at the local or territorial level, for actions and the mobilization of resources and socio-educational agents. The purpose of this essay is to present recommendations for the formulation of local plans address and prevent school absenteeism. It focuses on proposing basic conditions for the formulation of a local plan, such as the design of objectives in tune with a moral purpose, a preventive approach, and a collective work.